N-Acetylcysteine Reverses Monocrotophos Exposure-Induced Hepatic Oxidative Damage via Mitigating Apoptosis, Inflammation and Structural Changes in Rats - Jagjeet Singh; Annu Phogat; Chandra Prakash; Sunil Kumar Chhikara; Sandeep Singh; Vinay Malik; Vijay Kumar (Antioxidants, 2021)
Oxidative stress-mediated tissue damage is primarily involved in hepatic injuries and dysfunctioning. Natural antioxidants have been shown to exert hepatoprotective, anti-inflammatory and antiapoptotic properties. The present study evaluated the effect of N-acetylcysteine (NAC) against monocrotophos (MCP) exposure-induced toxicity in the rat liver. Albino Wistar rats were divided into four groups: (1) control, (2) NAC-treated, (3) MCP-exposure, (4) NAC and MCP-coexposure group. The dose of MCP (0.9 mg/kg b.wt) and NAC (200 mg/kg b.wt) were administered orally for 28 days. Exposure to MCP caused a significant increase in lipid peroxidation, protein oxidation and decreased glutathione content along with the depletion of antioxidant enzyme activities. Further MCP exposure increased pro-inflammatory cytokines levels and upregulated Bax and Caspase-3 expressions. MCP exposure also caused an array of structural alternations in liver tissue, as depicted by the histological and electron microscopic analysis. Thepretreatment of NAC improved glutathione content, restored antioxidant enzyme activities, prevented oxidation of lipids and proteins, decreased pro-inflammatory cytokines levels and normalized apoptotic protein expression. Treatment of NAC also prevented histological and ultrastructural alternations. Thus, the study represents the therapeutic efficacy and antioxidant potential of NAC against MCP exposure in the rat liver.